plssssssssssssssssssssssss answwr
Attachments:
![](https://hi-static.z-dn.net/files/d61/8ce681fd793bf187def2279c26621973.gif)
Answers
Answered by
1
Answer:
[(x-1)(x-2)(x²-9x+14)] / [(x-7)(x²-3x+2)]
= [(x-1)(x-2)(x²-2x-7x+14)] / [(x-7)(x²-x-2x+2)]
= [(x-1)(x-2){x(x-2)-7(x-2)}] / [(x-7){x(x-1)-2(x-1)}]
= [(x-1)(x-2)(x-7)(x-2)] / [(x-7)(x-1)(x-2)]
= x-2 [ since common terms got cancelled out ]
ans = (x-2)
hope it helped :)
Similar questions
Math,
3 months ago
Math,
3 months ago
Math,
6 months ago
Physics,
1 year ago
Environmental Sciences,
1 year ago